2020
DOI: 10.1038/s41467-020-18560-z
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative framework reveals ecological drivers of grassland microbial community assembly in response to warming

Abstract: Unraveling the drivers controlling community assembly is a central issue in ecology. Although it is generally accepted that selection, dispersal, diversification and drift are major community assembly processes, defining their relative importance is very challenging. Here, we present a framework to quantitatively infer community assembly mechanisms by phylogenetic bin-based null model analysis (iCAMP). iCAMP shows high accuracy (0.93–0.99), precision (0.80–0.94), sensitivity (0.82–0.94), and specificity (0.95–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
503
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 669 publications
(512 citation statements)
references
References 66 publications
9
503
0
Order By: Relevance
“…As β‐diversity often depends on community size (α‐diversity; Chase et al, 2011; Kraft et al, 2011; Myers et al, 2015), we also calculated the standard effective size of β‐diversity (i.e., β‐deviation) by comparing observed β‐diversity values to those generated by null models. We generated 999 null local communities within each N treatment, by randomly placing individuals into each local community with probabilities proportional to regional relative cover/abundance of the species, while preserving local α‐diversity (Ning et al, 2019, 2020). The standardized effect size (β‐deviation for Bray–Curtis and Jaccard dissimilarity) was calculated as the difference between the observed β‐diversity and mean β‐diversity of the null communities divided by the standard deviation of β‐diversity of the null communities (Kraft et al, 2011; Ning et al, 2019, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…As β‐diversity often depends on community size (α‐diversity; Chase et al, 2011; Kraft et al, 2011; Myers et al, 2015), we also calculated the standard effective size of β‐diversity (i.e., β‐deviation) by comparing observed β‐diversity values to those generated by null models. We generated 999 null local communities within each N treatment, by randomly placing individuals into each local community with probabilities proportional to regional relative cover/abundance of the species, while preserving local α‐diversity (Ning et al, 2019, 2020). The standardized effect size (β‐deviation for Bray–Curtis and Jaccard dissimilarity) was calculated as the difference between the observed β‐diversity and mean β‐diversity of the null communities divided by the standard deviation of β‐diversity of the null communities (Kraft et al, 2011; Ning et al, 2019, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We inferred community assembly mechanisms with a phylogenetic bin-based null model (iCAMP) [44] and found that dispersal limitation and homogenous selection were the key processes driving protist community assembly in both sampling sites during the five sampling times. Dispersal limitation had a larger effect on community assembly at the SL site (67-73%), followed by homogenous selection (23-29%) (Fig.…”
Section: Dispersal Limitation and Homogeneous Selection Shape Rhizospmentioning
confidence: 99%
“…The relative influences of community assembly processes were assessed by a phylogenetic bin-based null model framework, iCAMP, which was recently reported with substantially improved performance [44]. Briefly, iCAMP divided taxa into different phylogenetic groups (bins) to ensure adequate phylogenetic signal to infer selection from phylogenetic diversity; then, the processes (selection, dispersal, and drift or others) dominating each bin were identified, according to the deviation of observed phylogenetic and taxonomic diversity from random patterns simulated by null models; finally, the relative abundance of bins governed by each process was aggregated to evaluate its influence on entire community assembly.…”
Section: Inferring Community Assembly Mechanismsmentioning
confidence: 99%
“…The assembly of microbial community was calculated using a framework to quantitatively infer community assembly mechanisms through phylogenetic bin-based null model analysis (iCAMP) in iCAMP packages (version 1.2.9) under the default parameters with the argument of bin.size.limit = 24 (Ning et al, 2020). In detail, the bins were divided according to the phylogenetic relationships of observed taxa.…”
Section: Microbial Community Assemblymentioning
confidence: 99%